Heart inflammation - a complication of Covid 19 infection or vaccination? - Tomos, Sirma; Erimia, Cristina-Luiza; Margaritti, Doina; Busuricu, Florica (Technium BioChemMed, 2023)
Severe acute respiratory syndrome (SARS CoV2) is an unparalleled challenge for the global medical community. Although the main clinical manifestation is pulmonary, with variations ranging from asymptomatic to mild flu-like illness to severe pneumonia and acute respiratory distress syndrome with potential fatality. The essential mechanism consists of the binding of the virus to ACE2 receptors through a viral envelope protein (protein S or SPIKE) followed by the appearance of a serum protease TMPRSS2 which mediates the binding of the virus at the cellular level. Because ACE2 is a cell membrane peptidase in the lungs, heart, blood vessels, kidneys, brain and gastrointestinal tract, COVID19 infections can occur at any of these levels. All ACE2-expressing cells are at risk of infection. Currently, viral pericarditis associated with both SARS CoV2 infection and vaccination against this virus is becoming more and more common, regardless of the vaccine used. Since April 2021 in the US there have been over 1000 reports in VAERS of myocarditis and post-vaccination pericarditis m RNA Covid-19 (BioNTech, Modern). Although the frequency of myocarditis and pericarditis was rare post-vaccination - 0.0018% of cases reported between December 2020 and July 2021 - the number of cases is certainly much higher, these complications being underdiagnosed, and therefore incorrectly managed and treated[1]. In fact, government organizations also considered these complications, on June 23, 2021 the safety committee of the US Centers for Disease Control and Prevention stated that there is a likely association between Pfizer - BioNTech and Moderna vaccines and myocarditis and pericarditis in some young people (16 -24 years), but that the benefits clearly outweigh the risks[2] As a result of all these signals, the US Food and Drug Administration said it will add this risk to the mRNA vaccine fact sheets, although it considers that such complications are "extremely rare" and that "most cases have been mild"[3].